NILAI-NILAI PENDIDIKAN DALAM NOVEL PERTEMUAN DUA HATI KARYA Nh. DINI:TINJAUAN SOSIOLOGI SASTRA - Nanik Sumarlin (EDU-KATA, 2019)
The aims of the reseach are to describe the education value of religion, value of culture , the education value of morale and to describe the education value of social in “ Pertemuan Dua Hati” novel by Nh. Dini. This research is quantitative with descriptive analysis method. Data were collected by researcher where data was recorded and analyzed during periode of research to collect data from novel’s text, then it processed and further analyzed in detailed.The results of the researh are the values of education in Pertemuan Dua Hati” novel by Nh. Dini which are contain values of education as follow (1) the value of religion with indicators such are discipline in religious ritual, pray, grateful, and resignation, (2) the value of culture with indicators such are doing habits in the daily life and tradition, (3) the value of morale which is connected to responsibility, conscience, and duty, (4) the value of social which contains giving mutual aids, love and affection, care about social, and sensivity about others.